Penentuan Suksesor Bisnis Dengan Metode Simple Multi Attribute Rating Technique (SMART) Berdasarkan Teori ACE-MAN Untuk Mendukung Suksesi Bisnis di PT. X - Ulya Mubarak, Zaki; Rivani, Rivani (Bahtera Inovasi, 2023)
This research was conducted to formulate an assessment and selection of business successors based on objective criteria to support the business succession process at the company which runs a business in the distribution of pharmaceutical products and medical devices. This research uses a qualitative approach with descriptive methods. Data were collected by using several techniques such as literature study, in-depth interviews, distribution of questionnaires and data triangulation from three informants who were also respondents to evaluate potential successors. Candidate evaluation criteria are determined based on the ACE-MAN theory (Acceptable, Charismatic, Energetic, Managing, Achieving and Networking). The candidate evaluation formulation is analyzed by qualitative methods and Simple Multi Attribute Rating Technique (SMART) method to find the best candidate with the highest rating score based on ACE-MAN criteria. The result of the research conducted is that the company has started planning the business succession process. There is one candidate who obtains the highest rating results from three assessors after being processed by the SMART method based on the ACE-MAN criteria and also being able to fulfill the family cultural values applied in the company.